Tracheomegaly Secondary to Tracheotomy Tube Cuff in Amyotrophic Lateral Sclerosis: A Case Report - Lee, Dong Hoon (Medicine (Baltimore), 2015)
Tracheomegaly has not been reported in amyotrophic lateral sclerosis (ALS). Herein, the authors report a case of tracheomegaly secondary to tracheotomy tube cuff in a patient with ALS. To our knowledge, this is the first report of an ALS patient with tracheomegaly and of tracheomegaly being associated with tracheotomy tube cuff and home tracheotomy mechanical ventilator. The clinician should consider the possibility of tracheomegaly in the differential diagnosis, if a patient with ALS develops repeat air leakage around the tracheotomy tube or rupture of tracheotomy tube cuff.